2017
DOI: 10.1111/1541-4337.12298
|View full text |Cite
|
Sign up to set email alerts
|

Plant Polyphenols as Antioxidant and Antibacterial Agents for Shelf‐Life Extension of Meat and Meat Products: Classification, Structures, Sources, and Action Mechanisms

Abstract: Oxidative processes and meat spoilage bacteria are major contributors to decreasing the shelf-life of meat and meat products. Oxidative processes occur during processing, storage, and light exposure, lowering the nutritional and sensory value and acceptability of meat and generating toxic compounds for humans. Polyphenols inhibit oxidative processes in 3 ways: as reactive species scavengers, lipoxygenase inhibitors, and reducing agents for metmyoglobin. Thus, polyphenols are candidate antioxidants for meat and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
258
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(264 citation statements)
references
References 214 publications
1
258
1
4
Order By: Relevance
“…These activities can be attributed to the total phenol, quercetin, and (-)epi-catechin contents of the infusion (Figure 2), as well as the other identified phytochemicals distributed in the leaf, particularly the phenolic distribution on the epidermis and mid rib ( Figure 1). Polyphenols are the most studied plant antioxidant phytochemicals and have been shown to exhibit their antioxidant activities by reducing free radicals via donation of H-atom from their OH group/s (Papuc, Goran, Predescu, Nicorescu, & Stefan, 2017). (-) epi-catechin has been recognized as the most common flavonoids of green teas (Forester & Lambert, 2011;Kim, Quon, & Kim, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These activities can be attributed to the total phenol, quercetin, and (-)epi-catechin contents of the infusion (Figure 2), as well as the other identified phytochemicals distributed in the leaf, particularly the phenolic distribution on the epidermis and mid rib ( Figure 1). Polyphenols are the most studied plant antioxidant phytochemicals and have been shown to exhibit their antioxidant activities by reducing free radicals via donation of H-atom from their OH group/s (Papuc, Goran, Predescu, Nicorescu, & Stefan, 2017). (-) epi-catechin has been recognized as the most common flavonoids of green teas (Forester & Lambert, 2011;Kim, Quon, & Kim, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the growing knowledge on their bioactive values, use of plant phenolics as natural additives has recently gained interest in the food industry. Several studies demonstrated the potential of these antioxidant and antimicrobial compounds as food preservatives as well as functional food ingredients [9][10][11]. In this respect, phenolic acids, flavonoids and tannins have gained special attention over the last decades [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…Plant foods are a rich source of bioactive compounds known as phytochemicals which possess a variety of biological activities (antibacterial and antioxidant activities) and impart health benefits beyond basic nutrition (Sreeramulu & Raghunath, ). Among the wide range of phytochemicals, phenolic and flavonoid compounds have attained the substantial attention in different areas of application such as food, health, and pharmaceutical industries in the recent years (Papuc, Goran, Predescu, Nicorescu, & Stefan, ; Sivarajan et al, ).…”
Section: Resultsmentioning
confidence: 99%